Processes towards employment among persons with psychiatric disabilities: a study of two individual placement and support programmes in Sweden - Ulla Nygren; Urban Markström; Birgitta Bernspång (Scandinavian Journal of Disability Research, 2014)
Individual placement and support (IPS) has been found to be an effective intervention for rehabilitation to work in the field of mental health. Being as the principles used in IPS reflect core values in the concept of personal recovery, several other outcomes than just the percentage of clients gaining employment are of interest. The purpose of the study was to describe a number of unique processes and analyze these with a special concern for circumstances perceived as important for the individual IPS process. A collective instrumental case-study design was used and five cases were included. Data from three different sources were collected, both quantitative and qualitative. The findings illustrate how a relationship characterized by curiosity, interest and engagement in the individual client, positive risk-taking and time for reflected experiences resulted in processes of change. It was concluded that providing IPS is a type of specialized relationship-based work that includes advanced problem solving.